2017
DOI: 10.1002/14651858.cd003374.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-containing regimens for metastatic breast cancer

Abstract: Analysis 1.3. Comparison 1 Platinum vs non-platinum regimens (subgroup analysis 1: by treatment-comparisons assessing mTNBC), Outcome 3 Objective tumour response rate (assessable participants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 49 publications
0
36
1
2
Order By: Relevance
“…35 Our network meta-analysis, directly and indirectly, compared anthracycline vs C and anthracycline plus Pl vs Pl, and showed no significant improvement of pCR rates by adding anthracycline to NAT regimen. during systemic therapy for metastatic breast cancer 38 and in the neo-adjuvant setting for TNBC. 24 Our study also confirmed that Plcontaining regimens render a higher risk of febrile neutropenia and grade 3-grade 4 thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…35 Our network meta-analysis, directly and indirectly, compared anthracycline vs C and anthracycline plus Pl vs Pl, and showed no significant improvement of pCR rates by adding anthracycline to NAT regimen. during systemic therapy for metastatic breast cancer 38 and in the neo-adjuvant setting for TNBC. 24 Our study also confirmed that Plcontaining regimens render a higher risk of febrile neutropenia and grade 3-grade 4 thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while it is not entirely scientifically supported, it appears conceivable that PPI may affect the body pH by buffering the stomach, that is their main target [188]. 6.3) Melatonin (MT) in breast cancer.…”
Section: ) Hydrogen Ion Dynamics In Multiple Drug Resistance (Mdr) Imentioning
confidence: 99%
“…Many associated risk factors, either genetic, from BRCA1 and BRCA2 gene mutations, plus a wide array of other genetic derangements [3], and a multiplicity of environmental factors such as as age, obesity and estrogens, among many others [4] are involved in the onset of BC. In spite of significant advances in therapy, the overall results are not too successful up to the present time, especially in advanced disease [5,6]. This may indicate that a change towards a more comprehensive and perhaps radically different perspective is necessary in order to incorporate more rational and less toxic treatments, and at the same time foster a better understanding of this multifaceted disease.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin, which is a metal-based anticancer drug, has been extensively used as a chemotherapy medication for various kinds of cancers such as ovarian cancer, head and neck cancer, cervical cancer, breast cancer, bladder cancer, esophageal cancer, lung cancer, brain tumors and neuroblastoma [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Cisplatin works by interfering with DNA replication and inhibits the growth of cancer cells [ 22 ].…”
Section: Introductionmentioning
confidence: 99%